Partnership and relationship happiness in endometriosis related chronic pelvic pain: a multicenter case–control study - el Hadad, Samia; Schwartz, Alexandra Sabrina Kohl; Gassner, Clarissa; Haeberlin, Felix; von Orelli, Stephanie; Imesch, Patrick; Leeners, Brigitte (Frontiers in Psychology, 2024)
Partnership is an important resource in dealing with endometriosis related chronic pain. Hence, our objective was to assess partnership in the context of endometriosis and its symptoms, considering the perspectives of both individuals involved.The study was designed as a multi-center matched case-control study in Switzerland, Germany and Austria. Altogether 381 women with surgically/histologically confirmed endometriosis and 381 control women, 250 male partners of endometriosis-affected women and 229 of control women were evaluated. Partnership quality, partnership happiness, separation thoughts, and areas of conflict were evaluated through the Partnership Questionnaire and a validated list of conflict areas.Results: Quality of partnership was rated as high by 60.1% of the women with endometriosis and 66.7% of the control women, as well as by 45.8% and 50.2% of their respective partners. Women with endometriosis mentioned separation thoughts, mostly related to sexual satisfaction, more often (34.9%/28.3%) and experienced more partnership-related conflicts than control women. Chronic pain, dyspareunia, dissatisfaction with sexuality, fatigue, and infertility were significantly associated with partnership conflicts. Fatigue and infertility but not pain experiences were related to lower partnership quality. Male partners in both groups reported separation thoughts equally often. In men, a high intensity of pain experienced by their partner was associated with reduced partnership happiness.Given the significance of partnership in dealing with chronic diseases and the connection between symptoms of endometriosis and a decrease in partnership quality, it is essential to incorporate strategies that alleviate the negative impacts on relationships for both partners into medical support.